Prosthesis for the Afterlife in TT16, Luxor, Egypt - Herrerín, Jesús.
The Ramesside tomb of Panehsy (TT16) located in Dra Abu El-Naga (Luxor West Bank), consists of two decorated rooms and a passage of approximately 50 meters towards the burial shaft of the original owners. Abundant human remains were found in this passage. These human remains are the consequence of the continuous reuse of the tomb for secondary burials for over one thousand years after the original use of the tomb. The majority of the human remains were mummified but are now fragmentary and incomplete because of environmental issues and the actions of thieves who hacked up the bodies in search of amulets and other valuable objects.